Design of Dental Disease Knowledge Base Editor Dialog using ISR-Framework - Aridhanyati Arifin; Rahadian Kurniawan; Sri Kusumadewi; Andri Panca Purnama; Kukuh Eka Nugraha (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2022)
Dental disease is one of the health problems commonly found in Indonesia. Data from the Indonesian Health Authority indicates an imbalance between the number of handled dental cases and the number of dental specialists who treat them. Technological advances bring significant improvements in the quality of medical services. A reliable Group Decision Support System (GDSS) requires a knowledge base editor for expert knowledge acquisition. A critical aspect in building a knowledge base is the interactive interface design. The problem that often arises is that experts find it hard to use a system because the interface does not meet their expectations. In this study, we analyze the interface requirements for a knowledge base editor with a group of experts. The purpose is to report on the process of designing a knowledge base editor interface with a user-centered expert group using the Information Systems Research (ISR-Framework) framework. We conducted several Focus Group Discussions involving 20 dentists, one dental specialist, and one Information Technology Expert in the GDSS field. The repetitive characteristics of this method help increase the value of user satisfaction. The research results expectedly support the ISR framework as a guide for designing future knowledge acquisition applications.